Wave-resolving shoreline boundary conditions for wave-averaged coastal models. (September 2020) - Memmola, Francesco; Coluccelli, Alessandro; Russo, Aniello; Warner, John C.; Brocchini, Maurizio
Abstract: Downscaling broadscale ocean model information to resolve the fine-scale swash-zone dynamics has a number of applications, such as improved resolution of coastal flood hazard drivers, modeling of sediment transport and seabed morphological evolution. A new method is presented, which enables wave-averaged models for the nearshore circulation to include short-wave induced swash zone dynamics that evolve at the wave group scale (i.e. averaged over the short waves). Such dynamics, which cannot be described, by construction through wave-averaged models, play a fundamental role in nearshore hydrodynamics and morphodynamics. The method is based on the implementation of a set of Shoreline Boundary Conditions (SBCs) in wave-averaged models. The chosen set of SBCs allows for proper computation of the short-wave properties at a mean shoreline ( x l ) taken as the envelope of the actual shoreline. The suitability of the approach is assessed through implementation of the SBCs into the Regional Ocean Modeling System (ROMS) coupled to a spectral wave model (InWave for IG waves and SWAN for wind waves). As the aim is to assess the viability of the approach, the SBCs are implemented only through a one-way coupling to ROMS (i.e. ROMS forcing the SBCs). Four different test cases – with constant, periodic and bichromatic offshore forcing – are run to assess the model performances. The main results of the analysis are: (a) the proposed SBCs can well reproduce the shoreline motion and swash zone dynamics in there for all chosen tests (RMSE and BIAS less than 20 % up to a cross-shore resolution of 4.0 m ( L 0 ∕ 3 or L 0 ∕ 5 )) and (b) implementation of the SBCs allows ROMS to accurately simulate the swash zone flows even at a resolution 40 times coarser than that needed by ROMS with its own wet–dry routine to properly describe the same flows. The latter result clearly demonstrates the major computational advantage of using the proposed SBCs. We also show that most of the swash zone dynamics is due to the mean flow (i.e. incoming Riemann variable) and the local (at x l ) wave height. However, especially in the case of bichromatic waves, the swash zone water volume content also seems to play a crucial role.